Age related changes in the tunica media of the vertebral artery: implications for the assessment of vessels injured by trauma. Issue 2 (1st February 2001) - Johnson, C P; Baugh, R; Wilson, C A; Burns, J
Abstract : Aims —To provide an illustrated, detailed semiquantitative analysis of the important degenerative changes along the length of the vertebral artery so that pathologists faced with investigating a fatal arterial injury can identify important pre-existing wall abnormalities. Methods —Ten transverse annuli were taken along 34 vertebral arteries from 17 subjects and stained sections were prepared using haematoxylin and eosin and the picro-sirius red method. After routine microscopy, the elastic fibres, collagen, and smooth muscle nuclei in the tunica media were quantified using an eyepiece graticule. An estimate of the severity and extent of elastic tissue fragmentation, collagenous scarring, and intimal thickening/atheroma was then undertaken. Results —Smooth muscle counts remained constant along the artery but collagen counts were higher and elastic counts substantially lower within the intracranial segment. Elastic fibre fragmentation was recognised in infancy and was moderately advanced by early adulthood but considerable collagenous scarring developed later in life. Some individuals demonstrated severe fragmentation and scarring before the age of 35 years. The degenerative changes were often focal and spared the intracranial segment almost completely. Atheroma increased with age but was rarely severe and appeared not to worsen appreciably beyond the age of 40 years. An unusual arrangement of the collagenous tissue was described within the upper cervical loops. Conclusion —Damaged vertebral arteries need to be sampled extensively to allow a proper histological assessment. The picro-sirius red method was successful in delineating the fine connective tissue structure of the wall and early degenerative changes. An understanding of the age and site specific changes should allow the pathologist to recognise important pre-existing abnormalities more easily.